Penatalaksanaan Holistik Pasien Balita dengan Asma Persisten Ringan melalui Pendekatan Kedokteran Keluarga - Arinda Stefani; Diana Mayasari (Medula, 2020)
Asthma is a chronic respiratory disease based on chronic inflammation which results obstruction and hyperreaction of the respiratory tract as a result of the interaction between genetic, host, and environmental factors. Studies on the natural history of asthma show that nearly 80% of cases begin during the first 6 years of life. Asthma management must be continuous monitoring to achieve controlled asthma, doctors must manage patients holistically from various aspects to improve quality of life.  Implementation of family-based evidence based medicine by identifying risk factors, clinical problems, and patient management based on patient problem solving framework with patient centred and family approach. This study is a case report. Primary data were obtained through alloanamnesis, physical examination, home visits to complete family and psychosocial data, as well as the environment. Assessment based on holistic diagnostic from the beginning, process and in the end of thr study quantitatively and qualitatively. Patients under five with mild persistent asthma. Internal factors in cases such as genetic factors, age, and lack of awareness in avoiding trigger factors. External factors are lack of family knowledge about asthma and its complications and a dusty environment. Pharmacological and non-pharmacological interventions are carried out in the form of education in preventing asthma attacks in patients. The diagnosis and management of these patients has been carried out in a holistic, patient centered, family approach and based on several recent theories and studies. In the behavior change process, the patient and family have reached the adoption stage.